SISTEM PENGGAJIAN BERBASIS WEBSITE PADA KANTOR DESA SUKAMEKAR - William Hermawan; Zyad Rusdi; Wasino Wasino (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
Sukamekar Village is a village located in Sukawangi District, Bekasi Regency, West Java which has a village head as the village leader, Sukamekar village has employees who serve as secretaries who are in charge of recording employee data and employee attendance who are still using the absent form, using the form frequently there is an error such as missing paper, no attendance data and the financial officer in charge of making salary data is also still manual with a letter of responsibility, therefore the author wants to create a payroll system for the Sukamekar village to assist in the process of computerized attendance and salary management, the web language used is php and mysql as the base data. The payroll system has employee data, attendance data, salary data, tax data and salary data.